HUBUNGAN MOTIVASI BELAJAR DAN KEAKTIFAN DALAM ORGANISASI TERHADAP HASIL BELAJAR SISWA (STUDI KASUS: KELAS XI SMAN 2 KUTA) - PURWANTI, EKA VIRGIA; NILAKUSMAWATI, DESAK PUTU EKA; ASIH, NI MADE (E-Jurnal Matematika; Vol 7 No 4 (2018), 2018)
The success of student learning is influenced by several factors such as learning motivation and student activeness in the organization. Each factors has several indicators. This research aims to see the relationship of learning motivation and activeness in the organization of learning outcomes,as well as to know indicators have the greatest real impact. The data used is the primary data in the form of questionnaires distributed, and secondary data in the form of the results of student report cards grade XI IPA academic year 2016/2017 in SMAN 2 Kuta. The research method used to process the data using Canonical Correlation Analysis. The results showed that the factors of learning motivation have a real effect of 0.00000000 on student learning outcomes with the closeness of the relationship of 0.7462935.. While the activeness in the organization does not have a real effect on learning outcomes. Passion and desire are the indicators of learning motivation which have the greatest influence among the other indicators with the closeness of the relationship of 0.5798190.